2017
DOI: 10.1096/fj.201601253r
|View full text |Cite|
|
Sign up to set email alerts
|

LEF1‐mediated MMP13 gene expression is repressed by SIRT1 in human chondrocytes

Abstract: Reduced SIRT1 activity and levels during osteoarthritis (OA) promote gradual loss of cartilage. Loss of cartilage matrix is accompanied by an increase in matrix metalloproteinase (MMP) 13, partially because of enhanced LEF1 transcriptional activity. In this study, we assessed the role of SIRT1 in LEF1-mediated MMP13 gene expression in human OA chondrocytes. Results showed that MMP13 protein levels and enzymatic activity decreased significantly during SIRT1 overexpression or activation by resveratrol. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 48 publications
6
50
0
Order By: Relevance
“…5C,D). However, in contrast to cells overexpressing flSIRT1 or ΔSIRT1, cells overexpressing 75SIRT1 demonstrated a 20% increase in H3 acetylation and a twofold increase in p65 acetylation, indicating that 75SIRT1 is enzymatically inactive, as previously reported for chondrocytes and cartilage (Elayyan et al, 2017;Oppenheimer et al, 2012). Of note, pcDNA (expression vector) controls possess similar substrate acetylation states to those presented for flSIRT1 and ΔSIRT1, which might be related to possible saturation of the deacetylation activity beyond substrate availability.…”
Section: Deacetylase Activity Is Maintained In the δSirt1 Mutantsupporting
confidence: 59%
See 1 more Smart Citation
“…5C,D). However, in contrast to cells overexpressing flSIRT1 or ΔSIRT1, cells overexpressing 75SIRT1 demonstrated a 20% increase in H3 acetylation and a twofold increase in p65 acetylation, indicating that 75SIRT1 is enzymatically inactive, as previously reported for chondrocytes and cartilage (Elayyan et al, 2017;Oppenheimer et al, 2012). Of note, pcDNA (expression vector) controls possess similar substrate acetylation states to those presented for flSIRT1 and ΔSIRT1, which might be related to possible saturation of the deacetylation activity beyond substrate availability.…”
Section: Deacetylase Activity Is Maintained In the δSirt1 Mutantsupporting
confidence: 59%
“…Why the enzymatic activity of SIRT1 is disrupted during aging is, as yet, unclear, although several (not mutually exclusive) factors have been hypothesized to affect this activity; most notably, the availability of NAD in the cell and various translational and posttranslational modifications, such as alternative splicing, SIRT1 phosphorylation, ubiquitination or SUMOylation (Lynch et al, 2010;Sasaki et al, 2008;Peng et al, 2015;Yang et al, 2007). We previously found that, in human cartilage samples and mouse models of osteoarthritis (OA; an age-associated disease), inflammation induces reduced SIRT1 activity via its truncation by the lysosomal cysteine protease cathepsin B (Dvir-Ginzberg et al, 2011;Elayyan et al, 2017). Although cathepsins are typically bound to the acidic lumen of the lysosome (where they participate in protein recycling), exposure to pro-inflammatory mediators, such as TNFα, can drive lysosomal permeability (Guicciardi et al, 2000) and the subsequent release of cathepsins to the cytoplasm and nucleus, where they target cellular proteins and alter various cellular circuits, including epigenetic reprogramming and apoptosis (Dvir-Ginzberg et al, 2011;Duncan et al, 2008;Droga-Mazovec et al, 2008;Oppenheimer et al, 2012;Cirman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the aberrant SIRT1/AMPK/PGC-1α signaling was found in OA chondrocytes [11] . It has been shown that the diminished SIRT1 in OA [12] was critical for chondrocyte survival via downregulation of a potent pro-apoptotic protein, PTP1B [13] , or suppression of cartilage-degrading enzymes through modulation of the NF-κB pathway [14] , [15] . Given that Hcy is involved in mitochondrial dysfunction and downregulation of SIRT1/AMPK/PGC-1α may lead to OA, we sought to investigate whether elevation of Hcy caused mitochondrial dysfunction in cartilage via inhibition of SIRT1.…”
Section: Introductionmentioning
confidence: 99%
“…Later stages of OA with loss of expression of chondrocyte SIRT1 corresponded to higher levels of p53 and p53 acetylation, relative to age-matched controls (trauma patients without OA). In addition, Elayyan and colleagues provided evidence for a mechanistic link between SIRT1 and control of MMP-13 gene expression mediated by the LEF1 transcription factor in human OA chondrocytes 42 . Overexpression of SIRT1 resulted in suppression of MMP-13 and LEF1 as well as their induction by IL-1b.…”
Section: Timing Of Treatment Interventions Mattersmentioning
confidence: 99%